Sensory innervation of the lumbar 5/6 intervertebral disk in mice - Chen, Lunhao; Lu, Xuan; Jin, Qianjun; Gao, Zhihua; Wang, Yue (Frontiers in Neurology, 2023)
Introduction Over the years, most back pain-related biological studies focused on the pathogenesis of disk degeneration. It is known that nerve distributions at the outer layer of the annulus fibrosus (AF) may be an important contributor to back pain symptoms. However, the types and origins of sensory nerve terminals in the mouse lumbar disks have not been widely studied. Using disk microinjection and nerve retrograde tracing methods, the current study aimed to characterize the nerve types and neuropathway of the lumbar 5/6 (L5/6) disk in mice. Methods Using an anterior peritoneal approach, the L5/6 disk of adult C57BL/6 mice (males, 8–12 weeks) disk microinjection was performed. Fluorogold (FG) was injected into the L5/6 disk using the Hamilton syringe with a homemade glass needle driven by a pressure microinjector. The lumbar spine and bilateral thoracic 13 (Th13) to L6 DRGs were harvested at 10 days after injection. The number of FG+ neurons among different levels was counted and analyzed. Different nerve markers, including anti-neurofilament 160/200 (NF160/200), anti-calcitonin gene-related peptide (CGRP), anti-parvalbumin (PV), and anti-tyrosine hydroxylase (TH), were used to identify different types of nerve terminals in AF and their origins in DRG neurons. Results There were at least three types of nerve terminals at the outer layer of L5/6 AF in mice, including NF160/200+ (indicating Aβ fibers), CGRP+ (Aδ and C fibers), and PV+ (proprioceptive fibers). No TH+ fibers (sympathetic nerve fibers and some C-low threshold mechanoreceptors) were noticed in either. Using retrograde tracing methods, we found that nerve terminals in the L5/6 disk were multi-segmentally from Th13-L6 DRGs, with L1 and L5 predominately. An immunofluorescence analysis revealed that FG+ neurons in DRGs were co-localized with NF160/200, CGRP, and PV, but not TH. Conclusion Intervertebral disks were innervated by multiple types of nerve fibers in mice, including Aβ, Aδ, C, and proprioceptive fibers. No sympathetic nerve fibers were found in AF. The nerve network of the L5/6 disk in mice was multi-segmentally innervated by the Th13-L6 DRGs (mainly L1 and L5 DRGs). Our results may serve as a reference for preclinical studies of discogenic pain in mice.